Survival of Bipolaris sorokiniana (Sacc.) Shoemaker in soil and residue of wheat (Bangladesh Journal of Botany, 2008)
Off-season survival of Bipolaris sorokiniana (Sacc.) Shoemaker in sterilized and unsterilized soils, and in residues of wheat spread on soil surface were determined. Population of viable propagules of the fungus per gram of soil or residue was determined at monthly interval using dilution plate technique. It was found that the population of B. sorokiniana increased initially for two months in both soils and residues and declined thereafter. The decline was very sharp up to four months of survival and then onwards a gradual decline was observed. In case of free residue, a gradual decline in population was observed from the beginning of the pathogen survival. The pathogen could be recovered up to eight and ten months from the unsterilized and sterilized soil, respectively. It was not possible to recover the pathogen from the residues in unsterilized and sterilized soil after seven and eight months. The pathogen could survive for 12 months in free residue stored at room temperature. Â Â  Key words: Bipolaris sorokiniana, Survival, Soil, Residue, Wheat DOI = 10.3329/bjb.v36i2.1501 Bangladesh J. Bot. 36(2): 133-137, 2007 (December)